2022
DOI: 10.1021/acs.jmedchem.2c00117
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of S-217622, a Noncovalent Oral SARS-CoV-2 3CL Protease Inhibitor Clinical Candidate for Treating COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in millions of deaths and threatens public health and safety. Despite the rapid global spread of COVID-19 vaccines, effective oral antiviral drugs are urgently needed. Here, we describe the discovery of S-217622, the first oral noncovalent, nonpeptidic SARS-CoV-2 3CL protease inhibitor clinical candidate. S-217622 was discovered via virtual screening followed by biological scre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
411
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(465 citation statements)
references
References 35 publications
(69 reference statements)
8
411
1
Order By: Relevance
“…In this sense, multiple authors have suggested continuing studies of ivermectin and its interactions with the various targets of SARS-CoV-2 in order to use it as a model to guide efforts towards the development of new compounds and treatment strategies ( Tang and Dill, 1998 , Tang and Kaneko, 2020 , Toleikis et al, 2016 ) as has already been done ( Rabie, 2021 ). In fact, ivermectin is currently being investigated in the UK as part of the Platform Randomized Trial of Treatments in the Community for Epidemic and Pandemic Illnesses (PRINCIPLE), the world's largest clinical trial of possible COVID-19 treatments for recovery at home and in other non-hospital settings.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, multiple authors have suggested continuing studies of ivermectin and its interactions with the various targets of SARS-CoV-2 in order to use it as a model to guide efforts towards the development of new compounds and treatment strategies ( Tang and Dill, 1998 , Tang and Kaneko, 2020 , Toleikis et al, 2016 ) as has already been done ( Rabie, 2021 ). In fact, ivermectin is currently being investigated in the UK as part of the Platform Randomized Trial of Treatments in the Community for Epidemic and Pandemic Illnesses (PRINCIPLE), the world's largest clinical trial of possible COVID-19 treatments for recovery at home and in other non-hospital settings.…”
Section: Resultsmentioning
confidence: 99%
“…It is the first nonpeptidic, noncovalent SARS-CoV-2 M pro inhibitor clinical candidate for treating COVID-19. 12 It was discovered via virtual screening followed by biological screening of an in-house compound library and optimization of the hit compound using a structure-based drug-design strategy. S-217622 exhibited antiviral activity against a range of current outbreaks of SARS-CoV-2 variants and coronavirus families.…”
Section: Fluorinated Anti-covid-19 Drugsmentioning
confidence: 99%
“…2 Both aims have been achieved in record time, the latter initially being driven by the investigation into repurposing existing drugs, which has produced few effective treatment options. 3 The search for novel SARS-CoV-2 antivirals, on the other hand, has led to the development of molnupiravir by Merck, 4 EDP-235 by Enanta, 5 S-217622 by Shionogi, 6 and several others. 7 The first such antiviral to receive approval by the FDA, Paxlovid, is an orally-active combination of the SARS-CoV-2 main protease inhibitor nirmatrelvir (1; PF-07321332) and the HIV antiviral ritonavir, disclosed by Pfizer in late 2021.…”
Section: Introductionmentioning
confidence: 99%